Comprehensive genome sequence analysis of the devastating tobacco bacterial phytopathogen Ralstonia solanacearum strain FJ1003 - Chen, Kun; Zhuang, Yuhui; Wang, Lihui; Li, Huaqi; Lei, Taijie; Li, Mengke; Gao, Meijia; Wei, Jiaxian; Dang, Hao; Raza, Ali; Yang, Qiang; Sharif, Yasir; et al. (Frontiers in Genetics, 2022)
Due to its high genetic diversity and broad host range, Ralstonia solanacearum, the causative phytopathogen of the bacterial wilt (BW) disease, is considered a “species complex”. The R. solanacearum strain FJ1003 isolated from the Fuzhou City in Fujian Province of China, phylotype I. Interestingly, we found that it’s host specific and only infects tobacco, especially in the tropical and subtropical regions. To elucidate the pathogenic mechanisms of how FJ1003 infects tobacco, a complete genome sequencing of FJ1003 using single-molecule real-time (SMRT) sequencing technology was performed. The complete genome size of FJ1003 was 5.90 Mb (GC%, 67%), containing the chromosome (3.7 Mb), megaplasmid (2.0 Mb), and small plasmid (0.2 Mb). A total of 5133 coding genes (3446 and 1687 genes for chromosome and megaplasmid, respectively) were predicted. A comparative genomic analysis with other strains having the same and different hosts showed that the FJ1003 strain had 90 specific genes, possibly related to the host range of R. solanacearum. Horizontal gene transfer (HGT) was widespread in the genome, as a type Ⅲ effector protein (Rs_T3E_Hyp14) was present on both the prophage and genetic island (GI), suggesting that this gene might have been acquired from other bacteria via HGT. The research shows that Rs_T3E_Hyp14 is a virulence factor in the pathogenic process of R. solanacearum, which affects the pathogenicity and colonization ability of R. solanacearum in the host. Therefore, this study will improve our understanding of the virulence of R. solanacearum and provide a theoretical basis for tobacco disease resistance breeding.